Strain rate dependent mechanical response for monoclinic NiTi shape memory alloy: Micromechanical decomposition and model validation via neutron diffraction - Zhaolong Yang; Hong Wang; Yalin Huang; Xiangping Ye; Jian Li; Changsheng Zhang; Hongjia Li; Beibei Pang; Yi Tian; Chaoqiang Huang; Guangai Sun (Materials & Design, 2020)
Design of shape memory alloy based structure in high–frequency or dynamic applications needs to build on a luminous comprehension for high speed deformation mechanisms of the corresponding material. In present work, dynamic responses and bulk texture evolutions are studied in martensitic NiTi through multi–scale characterization efforts. The objective is to quantitatively decompose the macroscopic strain according to deformation mechanisms and construct a phenomenological constitutive model. This study uses quasi–static in–situ and dynamic ex–situ neutron diffraction techniques to follow the evolution of bulk texture, twin volume fraction, and active twinning modes under various strain rates. It is demonstrated that the mechanical responses are strongly rate sensitive. The observation is attributed to the variation in slip activity. A distinct twinning mode change during compression is captured through in–situ neutron diffraction, and the shear induced reorientation is well described. Based on experimental observations, a constitutive model that includes effects of elasticity, reorientation of accommodation twinning, and plasticity is constructed and validated in a wide strain rate range. The overall results provide insights into strain rate dependent mechanical response of martensitic NiTi in both experiment and model aspects. This work will guide the design and application of shape memory alloys, especially in dynamic condition.